The Effect of Supervision and Incentives on Employees’ Work Morale at the Regional Secretariat of Central Tapanuli Regency - Iramayasari Siahaan; Kaharuddin Kaharuddin; Mhd. Shafwan Koto (Journal of Economics, Management and Accounting (JEMA), 2026)
This study aims to determine the effect of supervision and incentives on employees’ work morale at the Regional Secretariat of Central Tapanuli Regency. The research method used in this study is a quantitative method with a descriptive approach. The population in this study consisted of employees at the Regional Secretariat of Central Tapanuli Regency, with a total sample of 91 respondents obtained through questionnaire distribution. The data analysis techniques used include validity test, reliability test, classical assumption test, multiple linear regression analysis, coefficient of determination, and hypothesis testing using the t-test and F-test. The results of the study show that the coefficient of determination (R²) value is 0.502, which means that 50.2% of the variation in employees’ work morale is jointly influenced by the supervision and incentive variables, while the remaining 49.8% is influenced by other factors not examined in this study, such as leadership, work environment, competence, facilities, coordination, and other factors. The results of the t-test indicate that supervision has a positive and significant effect on employees’ work morale with a t-count value of 2.489 greater than the t-table value of 1.98729 and a significance value of 0.015 less than 0.05. In addition, incentives also have a positive and significant effect on employees’ work morale with a t-count value of 5.775 greater than the t-table value of 1.98729 and a significance value of 0.000 less than 0.05. Furthermore, the results of the F-test show that the F-count value is 44.441 greater than the F-table value of 3.10 with a significance value of 0.000 less than 0.05. Thus, it can be concluded that supervision and incentives simultaneously have a positive and significant effect on employees’ work morale at the Regional Secretariat of Central Tapanuli Regency.